2019
DOI: 10.21077/ijf.2019.66.2.81002-17
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the orangefin ponyfish Photopectoralis bindus (Valenciennes, 1835) off Mangaluru coast, Karnataka

Abstract: The spawning periodicity of Photopectoralis bindus (Valenciennes, 1835) was studied off Mangaluru coast from September 2015 to April 2016 using 490 specimens with total length 6.8-12.3 cm (9.6±0.9 cm) and body weight 4.6 -30.28 g (14.20±3.59 g). Results indicated that the average sizes at maturity were 9.3 cm (males) and 9.5 cm (females). The male-female ratio was 1:0.72. Absolute fecundity estimated was 9349±853 eggs that increased with fish size (R2 = 0.92). Higher gonado-somatic index (GSI) was observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The figure of 54.88% was lower than that found in other studies of Indian mackerel (Rastrelliger kanagurta) that used truss morphology [13,20]. This may have been because the truss network system is highly effective at capturing creature shape [24]. However, this study used conventional morphometrics as part of our preliminary identification of the short mackerel population.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The figure of 54.88% was lower than that found in other studies of Indian mackerel (Rastrelliger kanagurta) that used truss morphology [13,20]. This may have been because the truss network system is highly effective at capturing creature shape [24]. However, this study used conventional morphometrics as part of our preliminary identification of the short mackerel population.…”
Section: Resultsmentioning
confidence: 60%
“…The morphometric measurements of the short mackerels; weight, total length, standard length, folk length, head length, post -orbital length, pre -dorsal length, pre -pelvic length, 1 st dorsal to 2 nd dorsal length, pelvic to anal length, pre -anal length, head depth, and greatest Khan province, Chumphon province, and Surat Thani province depth, were analyzed (Figure 2). These 12 morphometrics are common characteristics and have been the principal source of evidence for evolutionary and taxonomic investigations [24].…”
Section: Methodsmentioning
confidence: 99%
“…According to the morphometric and meristic characteristics, they found that there is high variation between the locality groups belonging to the samples of C. kais. Rawat et al (2017) studied the meristic characteristics and their variations among the population of splendid pony fish, Eubleekaria splendens, along the Indian coast. They claimed that depending on their locations and the coast, fish had different numbers of pectoral fin rays.…”
Section: Discussionmentioning
confidence: 99%
“…The morphometric characters of fish species are influenced by genotype and environmental factors. Moreover, identification of stock with pronounced phenotypic and genetic differentiation among fish populations within a species serves to facilitate managing the stock separately, to determine stock-wise population abundance, and to accomplish the objectives of fisheries stock assessment by modelling (Rawat et al 2017). Moreover, morphometric characters are considered to be phenetic characters (characters of adaptive variation) and habitat variables directly influence the phenotype of an organism (Vidalis et al 1997, Bears et al 2008, Pigliucci 2005.…”
Section: Introductionmentioning
confidence: 99%